Perencanaan Tebal Lapis Tambah (Overlay) Dengan Perbandingan Metode PD T-05-2005-B Dan Manual Perkerasan Jalan Nomor 02/M/BM/2013 - Iskandar, Iskandar; Wibisono, Gunawan; Elianora, Elianora (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Directorate General of Highways has issued many rules and guidelines in plotting the added layer thickness. These guidelines and rules continue to be improved and refined by DGH. Thisresearch will be discussed with the thickness of layers added by doing comparison method of Pd T-05-2005-B and Road Pavement Design Manual No. 02 / M / BM / 2013. The result of theanalysis showed that the accumulated equivalent value of sunburst standard of 10 years old age of 6,546,500.63 ESA. Differences in seasonal and temperature correction factors make theresult of the thickness of the layers added by two different methods. The result for thick layer added method Pd T-05-2005-B equal to 13,0 cm while for Road Pavement Design Manual No.02 / M / BM / 2013 equal to 8,6 cm.Keywords : Benkelman Beam, deflection, overlay